2015
DOI: 10.1111/pin.12317
|View full text |Cite
|
Sign up to set email alerts
|

Mass‐forming primary angiitis of central nervous system with Rosai‐Dorfmann disease‐like massive histiocytosis with emperipolesis

Abstract: Primary angiitis of the central nervous system (PACNS) is a vasculitis restricted to the CNS without systemic involvement. We report a case of PACNS that was radiologically tumor-mimicking, and pathologically similar to the Rosai-Dorfmann disease. A 20-year-old woman presented with a focal facial motor seizure. Magnetic resonance image revealed heterogeneously enhanced well-demarcated solitary cerebral mass in the posterior frontal lobe. Histopathologically, the lesion showed lymphoplasmacytic vasculitis with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…The solitary tumor-like mass lesions of PACNS are rare, which usually show high signal intensity on T2 and heterogeneously enhancing signals on Gd-enhanced images (17, 2226). Previously reported mass-forming PACNS cases in adults from 2000 to the present are summarized in the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…The solitary tumor-like mass lesions of PACNS are rare, which usually show high signal intensity on T2 and heterogeneously enhancing signals on Gd-enhanced images (17, 2226). Previously reported mass-forming PACNS cases in adults from 2000 to the present are summarized in the Table 1.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal in ND 100% [18] 100% [12] ND ND 100% [47] 100% [19] 100% [31] 100% [5] 100% [ x Kumar, 2017 [30] x Takahashi, 2017 [31] x x x Lee, 2017 [32] x x Arif, 2017 [33] x x x Mizuno, 2016 [34] x x Sun, 2016 [35] x x x Benson, 2016 [36] x x Pillai, 2016 [37] x x x Fang, 2015 [38] x x x Kim, 2015 [39] x X x Bajaj, 2015 [40] x x x Kim SI, 2015 [41] x Killeen, 2015 [42] x x x Gan, 2015 [43] x x Huang, 2015 [44] x x x Okunomiya, 2014 [45] x x Safouris, 2014 [46] x x x Michiels, 2014 [47] x x x x Gaillard, 2014 [48] x x Rao, 2014 [49] x x Noh, 2014 [50] x x x Safouris, 2013 [46] x x x Orr, 2013 [51] x x x Lyra, 2013 [52] x x Rosenberg, 2013 [53] x x Okeda, 2012 [54] x x Yu, 2011 [55] x…”
Section: Black Blood Mrimentioning
confidence: 99%
“… 40 However, Kim et al reported a case of PACNS that presented as a T2-hyperintense mass lesion, with some contrast enhancement on T1-weighted postcontrast imaging, in a 20-year-old woman presenting with seizures, highlighting the ability for PACNS to present in a similar manner to a primary CNS neoplasm. 33 A case series of four patients with PACNS-associated lesions reported by Lee et al demonstrated variable MRI findings, including inconsistent findings across DWI and PWI, in each patient, demonstrating the heterogeneity of the disease and the potential for diagnostic difficulties. 36 Similar mass lesions have been associated in other vasculopathies as well, including systemic lupus erythematosus, 41 and granulomatosis with polyangiitis has also been reported in the literature.…”
Section: Discussionmentioning
confidence: 95%